2010
DOI: 10.1021/ma101264k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Down of Color Transition Temperature of Thermochromically Reversible Bisdiynamide Polydiacetylenes

Abstract: A series of bisdiynamide lipids containing various lengths of methylene spacer (m = 2, 3 and 4) between the diynes and the diamide headgroup and number of methylene units (n = 6 and 9) in their hydrophobic tails are synthesized. All six lipids synthesized can be dispersed in water and photopolymerized by UV irradiation to give the corresponding polydiacetylene (PDA) sols. The color transitions from blue to red during heating-cooling cycles of the PDA sols are photographically recorded and monitored by UV-vis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 57 publications
4
49
0
Order By: Relevance
“…Many research groups have demonstrated that structural modification of head group and side chain is a very effective approach for tuning the colorimetric response of PDA assemblies [13][14][15]33,[44][45][46][47]. Comprehensive studies by Kim and coworkers have shown that the strength of interactions at PDA vesicle surface strongly dictates the color-transition temperature [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many research groups have demonstrated that structural modification of head group and side chain is a very effective approach for tuning the colorimetric response of PDA assemblies [13][14][15]33,[44][45][46][47]. Comprehensive studies by Kim and coworkers have shown that the strength of interactions at PDA vesicle surface strongly dictates the color-transition temperature [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the extreme cases where the interactions between head groups are very strong, the color transition of PDA assemblies, usually an irreversible process, changes to the reversible one. The structural modification by bonding the head groups together also yields PDA assemblies with reversible thermochromism [15,[45][46][47]. However, most of these works mainly focuses on the colorimetric response to temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Although some PDA system displayed reversible thermochromism, but in most of the cases reported earlier, reversible thermochromism was observed only in the narrow temperature range, for example 25-55 8C [33], or they were not fully reversible as they deteriorate to violet to red rather than blue to red after first heating-cooling cycle [34]. In the investigation described below, we prepared a new polydiacetylene, (Bip-PDA), in which biphenylcarboxylic acid group is connected in its side chain, the biphenyl group provides strong aromatic interaction between monomers and carboxylic acid induces intermolecular H-bonding during self-assembly.…”
Section: Introductionmentioning
confidence: 81%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] In the latter case, the applications rely on their ability to change colors in response to temperature, 15 pH, 16 receptors, [17][18][19][20][21] and other molecules 22 in a system. In addition, the flexibility of the precursors of polydiacetylenes to construct a variety of micro-or nanostructures (depending on the preparation methods) makes it possible to use them for the desired purposes.…”
Section: Introductionmentioning
confidence: 99%